Studi Kualitatif Phenomenology: Peran Radiografer Dalam Mengerjakan Pemeriksaan Radiologi Untuk Pasien Covid-19 - Falentina Syivasari (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Until now, Indonesia has become one of the countries with the highest health worker death rate in ASIA and the 3rd highest in the world due to exposure to COVID-19, reaching 647 people. Radiographers are one of the first lines of health professionals who are very likely to be exposed to COVID-19. The purpose of the study is to find out the adaptation of new radiographer habits during the COVID-19 pandemic including radiographer work experience, radiographer health conditions (including fisk and mental health) and radiographer resilience in pandemic times.Methods: Research design uses a qualitative approach with phenomenological types of research. The selection of informants is obtained from observations and interviews to radiographers. The study used purposive sampling techniques. Research instruments use observation sheets, interview guidelines and documentation study sheets. This research was conducted in the Radiology Unit at COVID-19 referral hospitals, public hospitals and private hospitals, around the city area of Surabaya, east Java. The data collection time is expected to be held in April - June 2021.Results: The results showed the work experience of radiographers before the pandemic period was very different from the experience during the pandemic. Radiographers experienced more convenience when working in the time before the pandemic. Much of the change lies in the use of personal protective equipment. The majority of respondents had high optimism about their health condition as well as a great sense of responsibility in caring for patients suspected of Covid-19. The majority of respondents continue to carry out the obligation to treat patients suspected of Covid-19 or who are confirmed positive for Covid-19 because it is an obligation for every radiographer. These differences include restrictions on the number of radiographers in the room, the use of PPE at level 3, and the screening process that must be done before examining patients.Conclusions: The role of radiographers is very important in carrying out radiological examinations, especially in pandemic times. Radiographers who are competent and comply with the SOP during the pandemic so as to minimize exposure to Covid 19.